Women's satisfaction with early home medical abortion with telephone follow-up: A questionnaire-based study in the UK. (August 2013) - McKay, R. J.; Rutherford, L.
Abstract : A questionnaire-based study was undertaken to assess women's satisfaction with the home medical abortion service. Over a 15-month period, questionnaires were conducted at 24 h and 2 weeks following the procedure. A total of 127 women took part in the study and filled in a questionnaire at 24 h, with 77 completing the questionnaire at 2 weeks. At 24 h, over 95% of women who responded, agreed or strongly agreed that they felt prepared for the pain and bleeding that they experienced at home. At 2 weeks, 97.3% of respondents felt that they had had enough information and knew what to expect, and were therefore satisfied with the procedure. Only 15% of women were lost to clinical follow-up at 2 weeks. The majority of women are satisfied with the home medical abortion service. These high satisfaction rates are maintained at 2 weeks. Telephone follow-up 2 weeks after the abortion was safe and effective.